The first troglobitic Pseudonannolene from Brazilian iron ore caves (Spirostreptida: Pseudonannolenidae) - Iniesta, Luiz Felipe Moretti; Ferreira, Rodrigo Lopes (Zootaxa, 2013)
Pseudonannolene spelaea n. sp. is the first strictly cave-dwelling species described for the family Pseudonannolenidae. It is found in iron ore caves in the Brazilian Amazon. The family Pseudonannolenidae is exclusively Neotropical and fre-quently found in caves of Brazil, from which 20 species are known. The new species is compared with its congeners and with related cave-dwelling species. The family Pseudonannolenidae is discussed, and comments are presented on the con-servation status of the caves where the species is found, which potentially may be the target of anthropogenic impacts re-sulting from iron ore extraction.